A comparison of phenytoin and valproate in previously untreated adult epileptic patients. Issue 1 (January 1982) - Turnbull, D M; Rawlins, M D; Weightman, D; Chadwick, D W
Abstract : Eighty-eight patients with the onset of epilepsy in adult life were randomly allocated to treatment with sodium valproate (600 mg/day), or phenytoin (300 mg/day), and followed up for at least 12 months. Both drugs were highly effective in the control of tonic-clonic seizures, irrespective of whether they were accompanied by focal features, but were markedly less effective in the control of partial seizures. Two patients exhibited acute allergic reactions to phenytoin. No significant differences have yet emerged in the efficacy of the two drugs, and valproate may be considered as a "fist-line" anticonvulsant in the treatment of adult onset epilepsy.